Implementasi Fungsi Kontrol dan Perekat Sosial RRI Pro 1 Bengkulu dalam Menjaga Eksistensi NKRI - Putri, Elezka Duwi; Budiman, Dwi Aji; Sari, Eka Vuspa (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
This research aims to determine the implementation of the control and social glue functions of RRI Pro 1 Bengkulu in maintaining the existence of the Republic of Indonesia. RRI Bengkulu, as part of RRI as well as a broadcasting institution, also helps realize Indonesia's national ideals because its broadcasts must be educational, ensuring the diversity and plurality of Indonesian society so that its integrity and existence are maintained within the Republic of Indonesia. Due to the low number of audiences, it is necessary to maximize the function of control and social glue so that audiences remain popular and reconcile them so that the existence of the Republic of Indonesia can be maintained. The research method uses a qualitative-descriptive approach with data collection techniques through interviews, documentation and literature studies. Research data is divided into two sources, namely primary and secondary data. The primary data for this research was obtained from interviews with informants as well as indirect secondary data. It aims to complement and support the primary data so that it is relevant to the research focus. The research results show that RRI Pro 1 Bengkulu carries out and implements social control and glue functions optimally through news and broadcast programs, including dialogue programs using social media like Instagram and YouTube. RRI Pro 1 Bengkulu has succeeded in implementing its control function by presenting accurate, balanced and critical information on various issues relevant to the existence of the Republic of Indonesia. Apart from that, the social glue role of RRI Pro 1 Bengkulu is reflected in various programs that promote culture, diversity and national values. In this context, RRI Pro 1 Bengkulu not only functions as a transmitter of information but also as an agent of social change that contributes positively to the formation of national identity and maintains unity amidst the dynamics of society. The implications of these findings provide new insights for the mass media and related stakeholders to continue to optimize their role in supporting the existence of the Republic of Indonesia. People get information or insight, and then various perspectives emerge. This diversity is tolerated, therefore the situation in society is conducive; it can be interpreted that society as a unified whole is maintained, and the existence of the Republic of Indonesia remains. The right decision is that RRI Bengkulu and its programs and RRI in the Republic of Indonesia region continue to carry out their broadcast programs in a sustainable manner by paying attention to aspects of adaptation to current changes, such as digitalization.